FILANTROPI DAN PELAYANAN RUMAH SAKIT BERBASIS GEREJAWI DALAM PERSPEKTIF HUKUM - Dyah Hapsari Prananingrum (Universitas Kristen Satya Wacana, 2018)
ABSTRACT The era of health decentralization and the era of national health insurance are the challenges for health services and hospitals organized by non-profit institutions. One of the non-profit institutions that hold hospitals is church. In history, Indonesia’s church-based hospitals have supported a lot in the field of health services. The strategy done by hospitals in order to be chosen by community must be developed and set in the direction to improve the quality of services, and consequently to be a smart, safe, and friendly hospitals. Also, it ought to maintain sophisticated and up-to-date supporting facilities and infrastructure and it must comply with effective and efficient management and operations principles. In addition, a strong funding sources are needed. A philanthropy may be necessary to conduct as an alternative fund while the existing laws permit the scheme of the philanthropy fund. Keywords: Indonesia Law, hospital, philanthropy